Ayer Hitam community participations in conservation: a conceptual paper - Shalihin, Mohd Shaiful Ehsan; Abd Rahman, Mohd Aizuddin (2020)
Introduction: Bullous pemphigoid is a rare acquired, chronic autoimmune blistering disease; which typically produces tense and large blisters with erosions on skin or mucous membrane. It is primarily affects elderly patients in the fifth to seventh decade of life and can be fatal, particularly in patients who are debilitated, with underlying medical problems or left untreated because of misdiagnosis. There are various factors documented able to facilitate bullous pemphigoid such as physical agents, viral infections and drug intake including gabapentin. Gabapentin is an anticonvulsant drugs, but also widely used in the management of neuropathic pain especially in primary care. Even it is rare, gabapentin has been found to cause bullous pemphigoid from the previous literatures. Nevertheless, the previous reported cases were mainly involving trunks and limbs; spared the oral cavity. Report: We herein report a case of a 66-year-old gentleman, who presented with swollen, itchy and tender upper and lower lips with localized erythematous macular rashes over left side of his face for two days duration. He had a history of taking oral gabapentin 300mg three times a day for one week prior to the onset of the lesions. The drug was prescribed in the primary care clinic for his neuropathic pain secondary to bilateral lower limb atherosclerotic gangrene. Examination revealed multiple bullous over his swollen upper lips with desquamative gingivitis. Other system examinations were unremarkable. The offending drug was immediately ceased and he was then referred to Dermatology team for further evaluation. Result: The diagnosis of Gabapentin-induced bullous pemphigoid was confirmed by clinical assessment and histopathological examination. His symptoms gradually improved after a week commencement of high potency topical corticosteroid. Conclusion: This case illustrates the importance of adequate physical examination including detailed oral examination to look for the pathognomonic features in a case suspected to be drug induced rashes. Indeed, adequate knowledge on the side effect of the possible medication that can induce catastrophe skin problem and prompt action to withhold the precipitating drug is really essential in primary care in order to save the pati ent’ s l i fe.